2000
DOI: 10.1017/s1357729800055107
|View full text |Cite
|
Sign up to set email alerts
|

The post-weaning behaviour of indoor-bred and outdoor-bred pigs

Abstract: The effect of two different lactation environments on the development of pig behaviour was examined at weaning and on days 1, 8, 15 and 57 post weaning. Ten focal indoor-bred pigs and 10 focal outdoor-bred pigs were weaned and mixed together into a group of 60 to 80 mixed indoor- and outdoor-bred pigs. There were six replicate groups. Scans of all focal animals were made using time sampling with a 2-min interval, for 3·0 h immediately following weaning and from 06:00 to 11:00 h on days 1, 8, 15 and 57 post wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
1
15
3
Order By: Relevance
“…This result is in contrast to Webster and Dawkins (2000), who did not find differences in skin blemish at slaughter between indoor and outdoor bred pigs. Mixing led to more unacceptable skin damage in the shoulder area and the whole carcass compared with non-mixing.…”
Section: Skin Damagecontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is in contrast to Webster and Dawkins (2000), who did not find differences in skin blemish at slaughter between indoor and outdoor bred pigs. Mixing led to more unacceptable skin damage in the shoulder area and the whole carcass compared with non-mixing.…”
Section: Skin Damagecontrasting
confidence: 99%
“…De Jong et al (2000) showed that pigs raised in barren housing tended to spend more time walking, standing and manipulating other pigs during transport than pigs from the enriched environment and in the lairage they tended to spend more time walking and fighting. However, Webster and Dawkins (2000) did not find differences in the level of skin blemish at slaughter between indoor and outdoor bred pigs.…”
Section: Introductioncontrasting
confidence: 60%
“…This could partly be explained by the long lactation period, which prevents the growth check at weaning that usually happens in conventional production with earlier weaning (English et al, 1988). It has been shown that piglets kept outdoors start to explore and eat dry food earlier than piglets kept indoors (Webster & Dawkins, 2000;Cox & Cooper, 2001). In addition, a lower infection load outdoors (Pig Management, 1995;Engblom, 1999) could be a contributing factor.…”
Section: Growth and Productionmentioning
confidence: 99%
“…In order to overcome this problem, diets especially designed for the digestive system of very young piglets have been formulated (Dritz et al, 1996). However, because the behaviour of piglets weaned at very young ages indicates distress and suffering (Weary et al, 2008), the age for weaning should not be defined solely based on the performance of the animals.When lactation takes place in enriched, as opposed to conventional housing environments, the piglets' responses to weaning generally involve lower frequencies of aggression and abnormal behaviours, and higher frequencies of playing, feeding and resting behaviours (Webster and -E-mail: mjhotzel@cca.ufsc.br 102 Dawkins, 2000;Cox and Cooper, 2001;Hö tzel et al, 2004), as well as higher growth rates in the post-weaning period (O'Connell et al, 2005). Some factors that may underlie the different behavioural responses to weaning in piglets reared in conventional or outdoor systems are the opportunity to contact piglets of other litters during lactation, which decreases fighting after weaning (Pitts et al, 2000;Weary et al, 2002), and the reduction in suckling frequency, which seems to encourage the piglets to explore solid food and spend time away from the sow (Hö tzel et al, 2004).…”
mentioning
confidence: 99%